Plasticity in inhomogeneously strained Au nanowires studied by Laue microdiffraction. (28th May 2018) - Ren, Z.; Cornelius, T.W.; Leclere, C.; Davydok, A.; Micha, J. -S.; Robach, O.; Richter, G.; Thomas, O.
ABSTRACT: Plasticity in as-grown gold nanowires deformed in three-point bending configuration was studied by Laue microdiffraction. One-dimensional orientation maps of the Au crystal along the nanowire were generated from which the deformation profile was inferred. The crystal lattice was found to rotate continuously around the Au [211] direction, which is transverse to the wire axis evidencing the storage of geometrically necessary dislocations (GNDs). The analysis of the diffraction peak shape points to the activation of multiple slip systems in contrast to the formation of wedge shaped twins predicted by MD simulations.